Tailoring PbTe quantum dot Size and morphology via ligand composition - Svetlana Lyssenko; Michal Amar; Alina Sermiagin; Ayan Barbora; Refael Minnes (Scientific Reports)
Abstract The literature shows a lack of significant research on the synthesis of large spherical PbTe quantum dots (QDs), particularly with controllable sizes and morphology. Here, we present for the first time a novel hot-injection method for the tunable, high-quality synthesis of cubooctahedral PbTe QDs within the size range of 10 nm to 16 nm. This method employs a combination of oleic acid (OA) with shorter carboxylic acids, including octanoic (OctA), decanoic (DA), and lauric acids (LA), tested at various volumetric ratios. Our investigation reveals that different ratios of these acids result in diverse morphologies. Lower concentrations (0.5:5.5 and 1:5) favor cubical morphologies while increasing the concentration of short ligands induces a transformation to cubooctahedral shapes. This shape change is associated with the disruption of nanocrystal (NC) crystallinity. Higher ratios of short ligands produce PbTe NCs with a crystallite core and an amorphous shell. Our findings demonstrate the tunability and precise control achieved with this mixed capping ligand hot-injection method, which significantly impacts QD applications in photovoltaics, electronics, and energy. Notably, shorter capping ligand (OctA) result in more monodispersed PbTe QDs, yielding larger cubooctahedral QDs up to 16 nm. Conversely, using capping ligands with lengths similar to OA leads to unstable and less tunable synthesis.